2012
DOI: 10.1021/jf3021877
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes of Starch during Baking and Staling of Rye Bread

Abstract: Rye sourdough breads go stale more slowly than wheat breads. To understand the peculiarities of bread staling, rye sourdough bread, wheat bread, and a number of starches were studied using wide-angle X-ray diffraction, nuclear magnetic resonance ((13)C CP MAS NMR, (1)H NMR, (31)P NMR), polarized light microscopy, rheological methods, microcalorimetry, and measurement of water activity. The degree of crystallinity of starch in breads decreased with hydration and baking to 3% and increased during 11 days of stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Bread crumb fi rmness underwent changes during storage. The chemical structure of wheat and rye is quite similar, so only small diff erences could be observed in starch retrogradation of rye and wheat bread (43). The structure of A-type starch switches into hydrated crystalline form after bread baking and during storage, but fermented rye bread was less crystalline.…”
Section: The Eff Ect Of Lactobacillus Reuteri On Bread Qualitymentioning
confidence: 99%
“…Bread crumb fi rmness underwent changes during storage. The chemical structure of wheat and rye is quite similar, so only small diff erences could be observed in starch retrogradation of rye and wheat bread (43). The structure of A-type starch switches into hydrated crystalline form after bread baking and during storage, but fermented rye bread was less crystalline.…”
Section: The Eff Ect Of Lactobacillus Reuteri On Bread Qualitymentioning
confidence: 99%
“…The long-range molecular structures of starch in the dough and steamed bread samples are shown in Figure 2 and Table 3. All the spectra exhibited strong diffraction peaks at about 2θ = 15°, 17°, 18°, and 23° (Figure 2a), indicating that the crystalline structures of the dough samples were of A-type pattern (Mihhalevski et al, 2012) and the type of crystalline structure was not affected by potato pulp added at different levels. However, the relative crystallinity of the dough samples added with different levels of potato pulp decreased significantly from 15.8% (0%) to 14.3% (10%), 12.8% (20%), 11.6% (30%), respectively, and the intensity of the peaks decreased with increasing potato pulp level.…”
Section: Xrd Analysismentioning
confidence: 99%
“…The NMR spectrum with CP and MAS was recorded at 100.613 MHz with a temperature of 295 K. A total of more than 6000 scans were accumulated for a spectrum with a recycle delay of 2s. For better studying the changes in the shortrange molecular orders of the potato starch samples, all the spectra were then decomposed into several peaks through deconvolution using PeakFit version 4.12 (Mihhalevski et al, 2012;Tan, Flanagan, Halley, Whittaker, & Gidley, 2007).…”
Section: C Cp/mas Nuclear Magnetic Resonance (Nmr) Spectroscopymentioning
confidence: 99%
“…Peaks at around 103 and 101.6 ppm in C1 region are typical characteristics of V-type single helices (eight glucose cycles per turn) (Baik, Dickinson, & Chinachoti, 2003;Mihhalevski et al, 2012;Tan et al, 2007;Tang & Hills, 2003), and 103 ppm is also related to amorphous starch content associated with the junction points of amylopectin double helices (Mihhalevski et al, 2012). By evaluating the changes in these peak areas, it is found that relative to native potato starch, the glow-plasma modified potato starch granules had less single helices which were further decreased by increasing the treatment time.…”
Section: Changes In Crystallinity and Short-range Ordermentioning
confidence: 99%